Endoscopic Ear Surgery: Tips and Pearls. (2nd September 2014) - Nogueira, João F.; Tarabichi, Muaaz; Marchioni, Daniele; Presutti, Livio; Pothier, David D.
Abstract : Program Description: Endoscopic ear surgery (EES) is a current hot topic in our specialty; however, it is not entirely correct to introduce EES as "new." Although not new, it is clear that during the past few years, endoscopes have proven to be safe and effective instruments to manage ear diseases in a minimally invasive way, preserving important anatomic structures, allowing functional approaches to well‐known conditions. Moreover, endoscopes have provided a better view and understanding of traditional middle ear anatomy and physiology, allowing new landmarks, novel concepts of tissue preservation, ventilation routes, and management of other conditions within the middle ear and beyond. Educational Objectives: (1) Describe the endoscopic anatomy of the middle and inner ears, discussing the concepts of related physiology. (2) Examine totally endoscopic and combined surgical approaches to middle ear conditions, discussing the possible advantages and disadvantages. (3) Present the instruments needed, system setup, surgical skills, learning curve, and also some important tips and pearls to surgeons to start doing endoscopic ear surgery.